Assessment of Soil and Water Conservation Potential Using Vetiver Crops (Chrysopogon zizanioides) as a Nature-Based Solution for Watershed Restoration - Chandra Setyawan; Yekti Nugraheni; Ngadisih Ngadisih; Rizki Maftukhah; Devi Safrina (The University of Lampung, 2025)
Watersheds play an important role in the hydrological cycle to ensure water availability and support food security. Currently, many watersheds are experiencing degradation due to excessive agricultural practices without the implementation of soil and water conservation measures. This study aims to assess the potential of Vetiver crops (Chrysopogon zizanioides L.) for soil and water conservation as a nature-based solution for watershed protection.n. This research use Geographic Information System (ArcGIS) tools to analyze land suitability for Vetiver cultivation. A multi-criteria evaluation approach was applied using a scoring system based on key environmental indicators including rainfall, temperature, slope gradient, land use type, soil type, and organic matter content. The results indicate that most of the study area was classified as moderately suitable (61.98%) and marginally suitable (38.00%) for vetiver plants, with only 0.01% falling into the highly suitable and not suitable categories, respectively. The integration of spatial analysis and environmental indicators allowed for the identification of priority areas where Vetiver could be effectively implemented to enhance watershed resilience, mitigate erosion, and support sustainable land management. The finding of this study provides a reference for vegetation method development using crops with economic value which is suitable for tropical areas.